Teacher Professionalism in Islamic Value-Based Character Education - Hanan Urwatin Nichla; Wahyu Isnatur Rohmah; Husni Umar Fadhilah; Shofiyatun Nasuha (Ilmina: Journal of Education and Counseling, 2026)
This study aims to examine teacher professionalism in character education based on Islamic values and its strategic role in shaping students with noble character. Teachers as professional educators are not only tasked with imparting knowledge, but also have the responsibility to instill moral and spiritual values in students. From an Islamic educational perspective, teacher professionalism is measured not only by pedagogical and academic competence, but also by personal integrity and the ability to internalize Islamic values in the learning process. Values such as honesty, trustworthiness, responsibility, exemplary behavior, and piety are the main foundations in building student character. This study uses a qualitative approach with a literature study type. Data were obtained from various library sources such as books, scientific journals, and laws and regulations relevant to the research topic. The results of the study indicate that teacher professionalism has a significant influence on the success of character education based on Islamic values. Teachers who have good pedagogical, personal, social, and professional competence based on Islamic values are able to create a conducive learning environment and shape student character optimally. Improving teacher professionalism integrated with Islamic values is essential to facing the challenges of modern education. This effort is expected to produce a generation that is not only intellectually superior but also possesses strong character and noble morals in accordance with Islamic teachings.